2001
DOI: 10.1128/jb.183.9.2859-2865.2001
|View full text |Cite
|
Sign up to set email alerts
|

Isogenic Strain Construction and Gene Targeting in Candida dubliniensis

Abstract: Candida dubliniensis is a recently described opportunistic fungal pathogen that is closely related to Candida albicans but differs from it with respect to epidemiology, certain virulence characteristics, and the ability to develop fluconazole resistance in vitro. A comparison of C. albicans and C. dubliniensis at the molecular level should therefore provide clues about the mechanisms used by these two species to adapt to their human host. In contrast to C. albicans, no auxotrophic C. dubliniensis strains are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…We constructed a URA auxotrophic strain CdJ3 by transforming Cd36 using the MPA flipper cassette (Staib et al 2001;see Methods). Next we replaced the CENPA-binding region of Chr7 (coordinates: CdChr7 434001-440600) of C. dubliniensis with the 1.4-kb URA3 sequence in the CdJ3 strain (Supplemental Fig.…”
Section: Formation Of Centromeric Chromatin On a Dna Sequence Is Contmentioning
confidence: 99%
“…We constructed a URA auxotrophic strain CdJ3 by transforming Cd36 using the MPA flipper cassette (Staib et al 2001;see Methods). Next we replaced the CENPA-binding region of Chr7 (coordinates: CdChr7 434001-440600) of C. dubliniensis with the 1.4-kb URA3 sequence in the CdJ3 strain (Supplemental Fig.…”
Section: Formation Of Centromeric Chromatin On a Dna Sequence Is Contmentioning
confidence: 99%
“…When MPA R was used in C. albicans, sometimes a high proportion of MPA-resistant transformants apparently had substituted the MPA R marker for the genomic IMH3 gene but did not contain the mutagenesis cassette inserted into the target gene locus (16). In contrast, when the MPA R marker was used for targeted gene inactivation in the related species Candida dubliniensis, virtually all MPA-resistant transformants had specifically integrated the cassette into the target locus, because the sequence divergence between the two species prevented integration of the C. albicans-derived MPA R marker into the orthologous C. dubliniensis IMP dehydrogenase gene IMD1 (14). These observations suggested that a similar MPA R marker derived from C. dubliniensis should also improve targeted insertion into the C. albicans genome.…”
mentioning
confidence: 99%
“…This product was also ligated with the SacII/XhoI fragment from pSFI1 to create the plasmid pCDR⌬2. C. dubliniensis was sequentially transformed by using approximately 1 g of the linear SacI/SphI fragments from plasmids pCDR⌬1 and pCDR⌬2 by electroporation as described by Staib et al (27). MPA-resistant transformants were selected on minimal medium agar plates containing 10, 15, or 20 g of MPA per ml.…”
mentioning
confidence: 99%
“…4), and this isolate was chosen in order to determine the influence of a CdCDR1 gene disruption on fluconazole susceptibility in this genetic background. For disruption of the CdCDR1 gene, a cassette (MPA R -flipper) containing the MPA resistance gene and the FLP site-specific recombinase fused to the inducible C. albicans SAP2 promoter (27), was inserted into the CdCDR1 ORF to create plasmids pCDR⌬1 and pCDR⌬2, thereby deleting the regions from nucleotide coordinates ϩ538 to ϩ4248 and ϩ1468 to ϩ3532, respectively (Fig. 5A).…”
mentioning
confidence: 99%